Analysis and Proposed of Performance and Measurement System Framework at Ministry of ESDM (The Indonesian Journal of Business Administration, 2013)
Since 2010, Ministry of Energy and Mineral Resources (ESDM – Energi dan Sumber Daya Mineral) was always awarded as one of the government institutions with the best LAKIP Report. While in the real life, the Ministry of ESDM kept on received criticize by parliament and public about its national ESDM management. If the LAKIP of Ministry of ESDM was truly evaluated and considered good, then supposed to be there wont be any unrest among parliament and public response about the national ESDM Management. This situation indicating that False alarm phenomena has occurred in the ministry. False alarm phenomena is a condition where the Ministry of ESDM feels successfully achieved their KPIs, but the public and other stakeholders do not feel an improvement in the management of energy and mineral resources. This research would focused, and limited, to the area of KPI and framework analysis. The design of ESDM Ministry’s Performance Measurement System (PMS) then analyzed through steps of PMS design. The ESDM Ministry’s PMS was also benchmarked with other government/non-profit organization’s PMS. Those analysis was resulted into the recommendation of Balanced Scorecard as the framework of the PMS. Keywords:PerformanceMeasurement, Balanced Scorecards, Non-Profit Organizations